A battleground of climate change: Summer air temperatures in social housing - Sebastian Pfautsch; Agnieszka Wujeska-Klause; Judi R. Walters; Abby Mellick Lopes; Louise Crabtree-Hayes; Emma Power; Bhavya Chitranshi; Helen Armstrong; Katherine Gibson; Cameron Tonkinwise; Stephen Healy (Urban Climate, 2026)

Managing Nutrition After Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy (CRS-HIPEC): A Qualitative Study of Colorectal Cancer Survivors’ and Caregivers’ Experiences - Kea Turner; Amir Alishahi Tabriz; Ryan Chi-Hsuan Su; Brent J. Small; Emma Hume; Olivia Sprow; Christina Santiago; Jennifer B. Permuth; Benjamin D. Powers; Jeremiah L. Deneve; Sean P. Dineen (Journal of the Academy of Nutrition and Dietetics, 2026)

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

Association of midlife air pollution and road proximity exposure with 29-year cognitive decline - Melinda C. Power; Ziwei Song; Annie Chen; Katie M. Lynch; Naa Adoley Parker-Allotey; Erin E. Bennett; Xiaohui Xu; Eric A. Whitsel; Richard L. Smith; James D. Stewart; Eun Sug Park; Qi Ying; et al. (NeuroToxicology, 2025)

Pre- and post-move exposure to air pollution and neighborhood socioeconomic status - Chelsea Liu; Erin E. Bennett; Katie M. Lynch; Xiaohui Xu; Eun Sug Park; Qi Ying; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Joel D. Kaufman; Emma K. Stapp; Melinda C. Power (Science of The Total Environment, 2025)

Preliminary evidence of a life stage specific antibody response to Cardicola spp. (Trematoda: Aporocotylidae) in ranched Southern bluefin tuna, Thunnus maccoyii - Maree Widdicombe; Melissa Carabott; Cecilia Power; Emma Wanicek; Daryl L. Evans; Paul A. Ramsland; Barbara F. Nowak; Nathan J. Bott (Fish & Shellfish Immunology, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Taking flight: An ecological, evolutionary and genomic perspective on bat telomeres - Megan L. Power; Nicole M. Foley; Gareth Jones; Emma C. Teeling (Molecular Ecology, 2022)
Over 20% of all living mammals are bats (order Chiroptera). Bats possess extraordinary adaptations including powered flight, laryngeal echolocation and a unique immune system that enables them to tolerate a diversity of viral infections without presenting clinical disease symptoms. They occupy multiple trophic niches and environments globally. Significant physiological and ecological diversity occurs across the order. Bats also exhibit extreme longevity given their body size with many species showing few signs of ageing. The molecular basis of this extended longevity has recently attracted attention. Telomere maintenance potentially underpins bats’ extended healthspan, although functional studies are still required to validate the causative mechanisms. In this review, we detail the current knowledge on bat telomeres, telomerase expression, and how these relate to ecology, longevity and life‐history strategies. Patterns of telomere shortening and telomerase expression vary across species, and comparative genomic analyses suggest that alternative telomere maintenance mechanisms evolved in the longest‐lived bats. We discuss the unique challenges faced when working with populations of wild bats and highlight ways to advance the field including expanding long‐term monitoring across species that display contrasting life‐histories and occupy different environmental niches. We further review how new high quality, chromosome‐level genome assemblies can enable us to uncover the molecular mechanisms governing telomere dynamics and how phylogenomic analyses can reveal the adaptive significance of telomere maintenance and variation in bats.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Perception of effort during an isometric contraction is influenced by prior muscle lengthening or shortening - Benjamin Kozlowski; Benjamin Pageaux; Emma F. Hubbard; Benjamin St. Peters; Philip J. Millar; Geoffrey A. Power (European Journal of Applied Physiology, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Long‐term nitrogen additions increase likelihood of climate stress and affect recovery from wildfire in a lowland heath - Georgina E. Southon; Emma R. Green; Alan G. Jones; Chris G. Barker; Sally A. Power (Global Change Biology, 2012)
Increases in the emissions and associated atmospheric deposition of nitrogen (N) have the potential to cause significant changes to the structure and function of N‐limited ecosystems. Here, we present the results of a long‐term (13 year) experiment assessing the impacts of N addition (30 kg ha −1 yr −1 ) on a UK lowland heathland under a wide range of environmental conditions, including the occurrence of prolonged natural drought episodes and a severe summer fire. Our findings indicate that elevated N deposition results in large, persistent effects on Calluna growth, phenology and chemistry, severe suppression of understorey lichen flora and changes in soil biogeochemistry. Growing season rainfall was found to be a strong driver of inter‐annual variation in Calluna growth and, although interactions between N and rainfall for shoot growth were not significant until the later phase of the experiment, N addition exacerbated the extent of drought injury to Calluna shoots following naturally occurring droughts in 2003 and 2009. Following a severe wildfire at the experimental site in 2006, heathland regeneration dynamics were significantly affected by N, with a greater abundance of pioneering moss species and suppression of the lichen flora in plots receiving N additions. Significant interactions between climate and N were also apparent post fire, with the characteristic stimulation in Calluna growth in +N plots suppressed during dry years. Carbon (C) and N budgets demonstrate large increases in both above‐ and below‐ground stocks of these elements in N‐treated plots prior to the fire, despite higher levels of soil microbial activity and organic matter turnover. Although much of the organic material was removed during the fire, pre‐existing treatment differences were still evident following the burn. Post fire accumulation of below‐ground C and N stocks was increased rapidly in N‐treated plots, highlighting the role of N deposition in ecosystem C sequestration.

Variable Responses of Lowland Tropical Forest Nutrient Status to Fertilization and Litter Manipulation - Emma J. Sayer; S. Joseph Wright; Edmund V. J. Tanner; Joseph B. Yavitt; Kyle E. Harms; Jennifer S. Powers; Michael Kaspari; Milton N. Garcia; Benjamin L. Turner (Ecosystems, 2012)

Effects of Human Trampling on Populations of Soil Fauna in the McMurdo Dry Valleys, Antarctica - EDWARD AYRES; JOHNSON N. NKEM; DIANA H. WALL; BYRON J. ADAMS; J. E. BARRETT; EMMA J. BROOS; ANDREW N. PARSONS; LAURA E. POWERS; BREANA L. SIMMONS; ROSS A. VIRGINIA (Conservation Biology, 2008)
Antarctic ecosystems are often considered nearly pristine because levels of anthropogenic disturbance are extremely low there. Nevertheless, over recent decades there has been a rapid increase in the number of people, researchers and tourists, visiting Antarctica. We evaluated, over 10 years, the direct impact of foot traffic on the abundance of soil animals and soil properties in Taylor Valley within the McMurdo Dry Valleys region of Antarctica. We compared soils from minimally disturbed areas with soils from nearby paths that received intermediate and high levels of human foot traffic (i.e., up to approximately 80 passes per year). The nematodes Scottnema lindsayae and Eudorylaimus sp. were the most commonly found animal species, whereas rotifers and tardigrades were found only occasionally. On the highly trampled footpaths, abundance of S. lindsayae and Eudorylaimus sp. was up to 52 and 76% lower, respectively, than in untrampled areas. Moreover, reduction in S. lindsayae abundance was more pronounced after 10 years than 2 years and in the surface soil than in the deeper soil, presumably because of the longer period of disturbance and the greater level of physical disturbance experienced by the surface soil. The ratio of living to dead Eudorylaimus sp. also declined with increased trampling intensity, which is indicative of increased mortality or reduced fecundity. At one site there was evidence that high levels of trampling reduced soil CO 2 fluxes, which is related to total biological activity in the soil. Our results show that even low levels of human traffic can significantly affect soil biota in this ecosystem and may alter ecosystem processes, such as carbon cycling. Consequently, management and conservation plans for Antarctic soils should consider the high sensitivity of soil fauna to physical disturbance as human presence in this ecosystem increases.

Ecosystem recovery: heathland response to a reduction in nitrogen deposition - SALLY A. POWER; EMMA R. GREEN; CHRIS G. BARKER; J. NIGEL B. BELL; MIKE R. ASHMORE (Global Change Biology, 2006)
Atmospheric deposition of nitrogen is responsible for widespread changes in the structure and function of sensitive seminatural ecosystems. The proposed reduction in emissions of nitrogenous pollutants in Europe under the Gothenburg Protocol raises the question of whether affected ecosystems have the potential to recover to their previous condition and, if so, over what timescale. Since 1998, we have monitored the response of a lowland heathland in southern England following the cessation of a long‐term nitrogen addition experiment, and subsequent management, assessing changes in vegetation growth and chemistry, soil chemistry and the soil microbial community. Persistent effects of earlier nutrient loading on Calluna growth and phenology, and on the abundance of lichens, were apparent up to 8 years after nitrogen additions ceased, indicating the potential for long‐term effects of modest nutrient loading (up to 15.4 kg N ha −1 yr −1 , over 7 years) on heathland ecosystems. The size and activity of the soil microbial community was elevated in former N‐treated plots, 6–8 years after additions ceased, suggesting a prolonged effect on the rate of nutrient cycling. Although habitat management in 1998 reduced nitrogen stores in plant biomass, effects on belowground nitrogen stores were small. Although some parameters (e.g. soil pH) recover pretreatment levels relatively rapidly, others (e.g. vegetation cover and microbial activity) respond much more slowly, indicating that the ecological effects of even small increases in nitrogen deposition will persist for many years after deposition inputs are reduced. Indeed, calculations suggest that the additional soil nitrogen storage associated with 7 years of experimental nitrogen inputs could sustain the observed effects on plant growth and phenology for several decades. Carry over effects on plant phenology and sensitivity to drought suggest that the persistence of vegetation responses to nitrogen deposition should be integrated into long‐term assessments of the impact of global climate change on sensitive ecosystems.